(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Since the formation of rights-based societies, women have been marginalized, portrayed as submissive to men, had their rights neglected, and have struggled to survive within a patriarchal system, where they are often victims of violence. Objective: To analyze Brazilian legislation and its role in combating violence against women, seeking to understand how the legal system has contributed to the creation of mechanisms for protection and the promotion of women’s dignity. Methods: A narrative literature review was conducted, analyzing scientific content, legislative documents, and institutional materials produced between 2006 and 2023. The search for materials was carried out in the SciELO and Google databases. Results: Significant progress was observed in Brazilian legislation, with highlights including the Maria da Penha Law (2006), the Femicide Law (2015), and the Sexual Harassment Law (2018), among others. These laws marked a new era in the struggle for women’s rights, promoting greater visibility and protection mechanisms. Conclusion: Despite advances, challenges remain, particularly regarding the realization of rights among Black, peripheral, and transgender women, who continue to face barriers in accessing services and legal support.